The Rhodes BioSure process in the treatment of acid mine drainage wastewaters - Corbett, Christopher John (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2001)
While sulphate-enriched wastewaters are generated in a number of industrial processes, such as tanning, paper manufacture and metals processing, the principal contributors to large-scale pollution from this source in South Africa are the gold and coal mining industries. Both biological and physico-chemical processes, set in train by mining operations, give rise to the oxidation of sulphur species, and the resultant generation of AMD. The Vaal River system is most affected and receives large tonnages of mining related salinity as both direct discharges, and in diffuse runoff flows. The long-term burden of this problem, and sustaining ongoing treatment over the time-frames involved will almost certainly resort to the community inhabiting the area, notwithstanding progressive mine closure legislation and comprehensive regulation governing the polluterpays principle. The volume and time-frame of the AMD problem, and the need for a long-term and sustainable response has focused interest in biological treatment approaches. These have concentrated on active and passive treatment systems, both of which rely on microbial activity related to the biological sulphur cycle. Notwithstanding the reactor type, and the particular treatment approach used, widespread application of active AMD treatment has not yet been seen on any large scale. Singular factors constraining process development are bioreactor design, cost of bioreactor construction, and the cost of the carbon source and electron donor for the biological sulphate reduction process. The SRB are able to utilise only a limited range of small organic molecules. The studies reported here were motivated by the need to evaluate low-cost options and the treatment of high volume AMD flows. This has focussed research activity on bioprocess developments using complex organic compounds derived from waste streams as electron donor sources, and the integration of AMD treatment with other waste treatment objectives. The co-disposal of organic wastes with AMD treatment would enable the development of an 'integrated resource management' approach to the problem, including sustainability of treatment operations over the long time-frames involved. Apart from the cost advantages accrued to waste treatment, the recovery of the treated water as a resource to the wider community provides a potentially important value-added function to the combined operation.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Uncatalogued